Vanuatu : 2006 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that following two years of contraction, output growth in Vanuatu recovered beginning in 2003, spurred by stronger performance in construction and a pickup in tourist arrivals. Growth reached 7 percent in 2005 and an estimated 5 1\2 percent in 2006, well above the average for Pacific island countries. The overall external balance has benefited from rising foreign direct investment, aid, and private capital inflows, with reserves increasing to more than 7 months of imports. If good macroeconomic policies continue and political stability is maintained, near-term prospects are positive.